A comprehensive gene expression profile of allergic rhinitis-derived nasal fibroblasts and the potential mechanism for its phenotype. (7th February 2022) - Li, Zhengwen; Zou, Wentao; Sun, Jingwen; Zhou, Shuang; Zhou, Yue; Cai, Xiaojing; Zhang, Jiaxiong
Background: Allergic rhinitis (AR) is a common immunoglobulin E-mediated immune response involved various cell types, while the role of nasal fibroblasts (NFs) in the pathogenesis of AR is less understood. Purpose: The study aimed to uncover the gene expression profile of AR-derived NFs and the potential mechanism for the changed phenotype of AR-NFs. Research Design: The primary NFs were isolated from 3 AR patients (AR-NFs) and 3 controls (Ctrl-NFs), and the proliferation, migration and interleukins production abilities of NFs were detected respectively. RNA-sequence was used to identify differentially expressed genes (DEGs) in AR-NFs. Transcription factor (TF) regulatory network and bioinformatic analyses were both conducted to clarify the biological roles of DEGs including the TFs. The DEG with the highest validated |fold change (FC)| value, detected by qPCR, was selected for further confirmation. Results: AR-NFs showed a higher proliferation and migration abilities as well as released higher levels of IL-33 and IL-6, compared to Ctrl-NFs. A total of 729 DEGs were screened out in AR-NFs. TF regulatory network indicated that BARX homeobox 1 (BARX1) and forkhead box L1 were the major node TFs. Bioinformatic analyses showed that a large number of DEGs including several target genes of BARX1 were both enriched cytokine-related GO terms, and immune- or inflammation-related pathways. BARX1 had the highest |FC| value, and silencing BARX1 in AR-NFs resulted in the significant downregulation of proliferation and migration abilities, and the production of interleukins. Conclusions: Our study for the first time provided the gene expression profile of AR-derived NFs, and BARX1 could be developed as a potent target to alleviate the pathogenesis of AR.